Aging Affects Subcortical Pitch Information Encoding Differently in Humans With Different Language Backgrounds - Liu, Dongxin; Hu, Jiong; Wang, Songjian; Fu, Xinxing; Wang, Yuan; Pugh, Esther; Henderson Sabes, Jennifer; Wang, Shuo (Frontiers in Aging Neuroscience, 2022)
Aging and language background have been shown to affect pitch information encoding at the subcortical level. To study the individual and compounded effects on subcortical pitch information encoding, Frequency Following Responses were recorded from subjects across various ages and language backgrounds. Differences were found in pitch information encoding strength and accuracy among the groups, indicating that language experience and aging affect accuracy and magnitude of pitch information encoding ability at the subcortical level. Moreover, stronger effects of aging were seen in the magnitude of phase-locking in the native language speaker groups, while language background appears to have more impact on the accuracy of pitch tracking in older adult groups.